An IoT-Based Smart Electronic Nose System for Non-Destructive Meat Freshness Monitoring - Nguyen, Thanh Huong; Le, Minh Hoang (JST: Engineering And Technology For Sustainable Development, 2024)
In recent years, food hygiene and safety violations have become a painful problem, especially in developing countries. It is essential to have tools or systems that can both monitor food quality and promptly warn users. Sensor technology as well as wireless communication technology pave the way to build a system that meets the above needs. In this paper, an electronic nose system based on the Internet of Things platform is proposed to monitor the freshness of food without changing the test sample. To evaluate the effectiveness of the proposed system, samples of three types of meat including pork, chicken and fish were collected and processed. In addition, the system also develops an application platform on smartphone devices to notify users about assessment results in real time. The system has been practically built and tested on product samples under many different testing conditions. The results show that the electronic nose system can effectively assess the freshness of meat through appropriate sensor parameters and provide timely warnings to the desired users.